ANALYSIS OF INDIRECT EXPENSES RATES - Daniela SIMTION (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The requirements of management work determine the functions, objectives and methods of the cost information system. In turn, these elements (functions, objectives, methods) generate the informational structure for presenting the respective elements. Indirect expenses contribute adjacent to the support of current activities. In general, these expenses are not easily identified when manufacturing a product, providing direct services or meeting the direct requirements of a project. Instead, indirect expenses are accrued in detailed accounting records, allocated and reported by each firm. The expenses are then cumulated in centralized documents at departments level (production, quality assurance, administrative, sales, research and development) according to the organizational requirements. Their analysis can help us assess indirect spendings and control excessive spending. The key factors in monitoring these expenses are continuous surveillance, control measures and performance measurement.